Development Of Cooperative Web-Based E-Learning For Mastery Of Computer Applications In The Academy Jambi Health Analyst - Nopindra, Alpari (Program Magister Teknologi Pendidikan Universitas Jambi, 2019)
In the 21st century era of globalization, free competition and rapid change demand quality human resources (HR) with high adaptability. The quality education process is crucial, and the role of teachers is very important in implementing learning. The Jambi Provincial Health Analyst Academy, as the only Diploma III Health Analyst institution there, is under the auspices of the Jambi Provincial Health Service. Adapting to educational reform and developments in science and technology, the Jambi Province Academy of Health Analysts plays a role in developing educational science in the field of science and technology. The Health Analyst Diploma III Program at the Jambi Province Health Analyst Academy aims to produce health analysts who are able to work as technical implementers of laboratory services. This research uses the Research and Development (R&D) method with a model adapted from Borg and Gall (1989). Validation was carried out by media and material experts, with excellent final results. Material validation results reached 93%, while trials on students also received satisfactory results, reaching 93% and included in the Very Eligible category. Thus, efforts to develop education in Jambi Province have a positive impact in creating quality human resources who are ready to compete in this era of globalization.